A decorative waterproof integrated coating and its production process

By mixing the homemade polymer emulsion with a specific ratio of cement, a paint with decorative and waterproofing is prepared, which solves the problems of poor compatibility and slurry pooling and deposition of the polymer cement waterproof coating film during use, and achieves the high-performance waterproofing effect of the coating film.

CN119286335BActive Publication Date: 2025-03-07GUANGZHOU AISHANI BUILDING MATERIALS TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411831283.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-07
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

During the use of polymer cement waterproof coating, there are problems such as poor compatibility, slurry polydeposition, poor calcium ion stability, and easy cracking of the coating film, resulting in failure of the waterproof effect.

Method used

Using homemade polymer emulsion, a paint with decorative and waterproofing is prepared by adding diisobutyl nylonate, aqueous resin dispersant K491, aqueous defoamer DT-650 and other additives, and mixing it with cement in a specific proportion.

Benefits of technology

It improves the waterproof performance of polymer cement, enhances the compatibility, mechanical stability and waterproof and permeability of the coating film, and avoids the problem of coating film cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286335B_ABST
    Figure CN119286335B_ABST
Patent Text Reader

Abstract

The present application relates to the field of coating technology, and specifically discloses a decorative waterproof integrated coating and its production process. A decorative waterproof integrated coating, with isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid, 3-methacryloxypropyl triisopropoxy silane as monomers, a polymer emulsion is prepared by an initiator and a compounded emulsifier, and then with diisobutyl nylonate as a film-forming agent, calcium carbonate whiskers, nano-silicon dioxide and dolomite powder as fillers, and inorganic pigments as colorants, by adding auxiliary agents, water-based resin dispersant K491 and 3 parts of water-based defoamers DT-650, and cement is mixed in a specific ratio to prepare a coating that is both decorative and waterproof. The decorative waterproof integrated coating prepared in this application has the characteristics of large tensile strength, high elongation at break, strong bonding strength, and excellent waterproof and anti-seepage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coating technology, and more specifically, to a decorative waterproof integrated coating and a production process thereof. Background Art

[0002] In the rapid development of construction projects in my country, waterproofing and anti-seepage are an important part. Among the many waterproof protection measures, waterproofing protection through surface coating is a widely used protection measure. Surface coating has a low economic cost and can be directly applied to the concrete surface. Polymer cement waterproof coating is a new type of green waterproof coating. It not only overcomes the disadvantages of environmental pollution caused by the use of volatile organic compounds, but also has strong tensile strength, durability and water resistance, and also has the flexibility and high tensile properties of polymers. It occupies a large market share in coating waterproof materials.

[0003] After years of use and research, it was found that polymer cement waterproof coating has made great progress in product performance and construction performance, but there are still some shortcomings in the use process: (1) The compatibility of polymer emulsion and cement powder is poor, and the slurry is prone to coagulation after a period of stirring; (2) During the stirring process, due to the poor stability of calcium ions, the organic and inorganic phases are separated during the curing process, which reduces the performance after mixing and causes microstructural defects; (3) The elongation at break of the formed coating is low, and the coating is prone to cracking due to the settlement, displacement, thermal expansion and contraction of the building, resulting in the failure of the coating waterproofing effect. Summary of the invention

[0004] In order to further improve the waterproof performance of polymer cement, the present application provides a decorative waterproof integrated coating and a production process thereof.

[0005] In the first aspect, the present application provides a technical solution using the following:

[0006] A decorative waterproof integrated coating comprises the following components by weight: 70-80 parts of polymer emulsion, 68-75 parts of cement, 4-6 parts of diisobutyl nylonate, 1-1.5 parts of water-based resin dispersant K491, 3-5 parts of water-based defoamer DT-650, 2.5-3.5 parts of inorganic pigment, 15-18 parts of filler and 10-15 parts of water.

[0007] By adopting the above technical scheme, using homemade polymer emulsion, nylon acid diisobutyl ester as film-forming agent, calcium carbonate whiskers, nano-silicon dioxide and dolomite powder as fillers, and inorganic pigments as colorants, by adding auxiliary agents water-based resin dispersant K491 and 3 parts of water-based defoaming agent DT-650, and mixing with cement in a specific proportion, a coating with both decorative and waterproof properties is prepared.

[0008] Preferably, the polymer emulsion is prepared by the following steps: S1, taking 55-65wt% of raw materials, mixing, stirring and dispersing at 40-50°C for 8-10min to obtain a pre-emulsion; the raw materials include deionized water, disodium sulfosuccinate ethoxylated alcohol half ester, allyloxy cardanol sulfonate, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid and 3-methacryloxypropyl triisopropoxy silane; S2, mixing the remaining raw materials and (25-35)wt% of initiator, heating to 78-82°C, stirring for 20-30min to obtain a seed emulsion; S3, dropping the remaining initiator and pre-emulsion into the seed emulsion, stirring and reacting for 30-45min after the dropping is completed, then heating to 85-90°C, keeping the temperature for 5-10min, naturally cooling to room temperature, adjusting the pH value to within 7.0-8.0, filtering, collecting the filtrate, and obtaining a polymer emulsion.

[0009] By adopting the above technical scheme, using isooctyl acrylate as a soft monomer, methyl methacrylate as a hard monomer, adding dodecyl acrylate with a long alkyl chain, allylmalonic acid with an ortho-carboxyl structure, and 3-methacryloxypropyltriisopropoxysilane with free radical activity, slow hydrolysis and easy emulsification as functional monomers, and adding an emulsifier prepared by a specific proportion of disodium ethoxylated alcohol sulfosuccinate and allyloxycardanol sulfonate, a polymer emulsion with the characteristics of high conversion rate, low gel rate, low water absorption rate, strong stability, moderate viscosity and good hydrophobicity is prepared, and the coating is prepared with cement and inorganic pigments without precipitation, and the prepared coating film has excellent mechanical properties.

[0010] Preferably, the dosage ratio of the deionized water, ethoxylated alcohol half sulfosuccinate disodium, allyloxy cardanol sulfonate, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid, 3-methacryloxypropyl triisopropoxy silane, and initiator is: (150-180) mL: (2-2.5) g: (0.40-0.6) g: (54-72) g: (15-26) g: (2.5-3.8) g: (3.2-4.7) g: (4.1-5.3) g: (0.3-0.6) g.

[0011] By adopting the above technical scheme, by adding allylmalonic acid with adjacent carboxyl groups, the probability of chelation with calcium ions in cement hydration is increased, so that the organic polymer phase, cement particles and hydration products form a tight structure that penetrates and fuses each other, thereby improving their compatibility, improving their physical properties through strong intermolecular forces, and improving the physical properties of the waterproof coating. The long alkyl chain of dodecyl acrylate can protect the ester group, prevent itself and the surrounding ester groups from hydrolyzing, and enhance its water resistance. Its long chain structure also reduces the viscosity of the emulsion by reducing the entanglement between polymer chains, and improves the cohesive strength and mechanical stability. During the emulsion film formation process, the isopropoxy group in 3-methacryloxypropyltriisopropoxysilane can undergo hydrolysis and condensation reactions with some active groups on the interface to generate a cross-linked structure, which makes the surface structure of the latex film tighter and reduces its water absorption through the hydrophobic group silicon oxygen bond. The emulsifier system composed of disodium sulfosuccinate ethoxylated alcohol half ester containing anionic and non-ionic emulsifying groups and allyloxy cardanol sulfonate with both reactive and emulsifying properties can enhance the polymerization stability, cement compatibility and mechanical stability of the emulsion.

[0012] Preferably, the initiator is dimethyl azobisisobutyrate.

[0013] By adopting the above technical solution, the initiator only produces one kind of free radical during the thermal decomposition process, and it is not easy to react with the solvent to cause side reactions such as chain transfer, and there is no induced reaction, and the molecular weight distribution of the obtained macromolecule is narrow.

[0014] Preferably, in S3, sodium bicarbonate is used to adjust the pH.

[0015] Preferably, the cement is white Portland cement.

[0016] Preferably, the filler is calcium carbonate whisker, nano-silicon dioxide and dolomite powder; the mass ratio of calcium carbonate whisker, nano-silicon dioxide and dolomite powder is (20-30) g: (10-12) g: (3-5) g.

[0017] By adopting the above technical solution, the proportion of fillers can make the pigment particles in the paint evenly distributed, so as to maximize the coloring ability of the pigment. At the same time, the paint can have good rheological properties, which is convenient for film construction and forms a smooth and flat coating film.

[0018] Preferably, the inorganic pigment includes one or more of ultramarine blue, zinc iron yellow, zinc iron chrome brown, and chromium oxide green.

[0019] By adopting the above technical solution, the above inorganic pigment has good compatibility with the polymer emulsion, and the color of the decorative waterproof integrated coating can be adjusted.

[0020] In a second aspect, the present application provides a production process for a decorative waterproof integrated coating, comprising the following steps: (1) mixing and grinding a filler, an inorganic pigment and an aqueous resin dispersant K491 for 10-20 minutes to obtain a colored filler; (2) placing a polymer emulsion in a mixer, and in a stirring mode, adding the colored filler, diisobutyl nylonate and water in sequence, continuing to stir for 3-5 minutes, then adding cement, continuing to stir for 1-3 minutes, and finally adding an aqueous defoamer DT-650, and continuing to stir for 5-8 minutes; the stirring speed is 200-300 rpm.

[0021] In summary, this application has the following beneficial effects:

[0022] 1. This application adopts a self-made polymer emulsion, with diisobutyl nylon acid as a film-forming agent, calcium carbonate whiskers, nano-silicon dioxide and dolomite powder as fillers, and inorganic pigments as colorants. By adding auxiliary agents, water-based resin dispersant K491 and 3 parts of water-based defoaming agent DT-650, and mixing with cement in a specific proportion, a coating with both decorative and waterproof properties is prepared.

[0023] 2. In the present application, isooctyl acrylate is preferably used as the soft monomer and methyl methacrylate is used as the hard monomer. By adding lauryl acrylate with a long alkyl chain, allylmalonic acid with an ortho-carboxyl structure, and 3-methacryloxypropyltriisopropoxysilane with free radical activity, slow hydrolysis and easy emulsification as functional monomers, and by adding an emulsifier prepared by a specific proportion of disodium sulfosuccinate ethoxylated alcohol half ester and allyloxycardanol sulfonate, a polymer emulsion with the characteristics of high conversion rate, low gel rate, low water absorption rate, strong stability, moderate viscosity and good hydrophobicity is prepared. The coating is prepared with cement and inorganic pigments without precipitation, and the prepared coating has excellent mechanical properties.

[0024] 3. The decorative waterproof integrated coating produced by the production process of the present application has the characteristics of high tensile strength, high elongation at break, strong bonding strength, and excellent waterproof and anti-seepage properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 : Infrared spectrum of the polymer emulsion prepared in Example 1 of the present application.

[0026] Figure 2 : Compatibility test diagram of the polymer emulsion of the present application and cement, wherein a is Example 3 and b is Comparative Example 5.

[0027] Figure 3 : The coating film is prepared using the decorative waterproof integrated coating of Examples 1 to 3 of the present application, with Example 1 on top, Example 3 in the middle, and Example 2 on the bottom. DETAILED DESCRIPTION

[0028] The present application is further described in detail below in conjunction with embodiments.

[0029] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0030] Example 1

[0031] A decorative waterproof integrated coating comprises the following components by weight: 70 parts of polymer emulsion, 68 parts of cement, 4 parts of diisobutyl nylonate, 1 part of water-based resin dispersant K491, 3 parts of water-based defoamer DT-650, 2.5 parts of inorganic pigment, 15 parts of filler and 10 parts of water.

[0032] The filler is calcium carbonate whisker, nano silicon dioxide and dolomite powder; the mass ratio of the calcium carbonate whisker, nano silicon dioxide and dolomite powder is 20g:10g:3g.

[0033] The inorganic pigment is ultramarine blue.

[0034] The cement is white silicate cement.

[0035] The polymer emulsion is prepared by the following steps:

[0036] S1, taking 55wt% of raw materials, mixing, stirring (stirring speed 1200r / min) and dispersing at 40°C for 8min to obtain a pre-emulsion; the raw materials include deionized water, disodium sulfosuccinate ethoxylated alcohol half ester, allyloxy cardanol sulfonate, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid and 3-methacryloxypropyl triisopropoxy silane;

[0037] S2, mixing the remaining raw materials and 25wt% of an initiator, raising the temperature to 78°C, and stirring at a speed of 500r / min for 20min to obtain a seed emulsion; the initiator is dimethyl azobisisobutyrate;

[0038] S3, add the remaining initiator and pre-emulsion dropwise into the seed emulsion. After the addition is complete, stir the reaction at a speed of 300 r / min for 30 minutes, then heat to 85°C, keep warm for 5 minutes, and naturally cool to room temperature. Use sodium bicarbonate as a buffer to adjust the pH value to within 7.0, filter, and collect the filtrate to obtain a polymer emulsion.

[0039] The deionized water, disodium sulfosuccinate ethoxylated alcohol half ester, allyloxy cardanol sulfonate, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid, 3-methacryloxypropyl triisopropoxy silane, and initiator are used in the following ratios: 150 mL: 2 g: 0.4 g: 54 g: 15 g: 2.5 g: 3.2 g: 4.1 g: 0.3 g. The model of allyloxy cardanol sulfonate is DNS-86, the effective content is 25%, and the manufacturer is Guangzhou Double Bond Trading Co., Ltd.

[0040] (11) Infrared spectrum test of polymer emulsion

[0041] Take 1.5mL of polymer emulsion and dilute it 10 times, take 1g from it, mix it evenly with 10g of potassium bromide powder, dry it in vacuum for 5h, grind it, press it into tablets, and use Fourier transform infrared spectrometer to perform infrared test. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that at 2952cm -1 The stretching vibration absorption peak of methyl (-CH3) appears at 2870cm -1 The vibration absorption peak of methylene (-CH2-) appears around 1731, and the stretching vibration absorption peak of carbonyl (-CO-) appears around 1242cm -1 Left and right 1160cm -1 The left and right sides are the characteristic peaks of COC stretching vibration in the ester group, 1063cm -1 The absorption peaks of silicon-oxygen-silicon bonds (Si-O-Si bonds) are at 837 cm -1 The absorption peak of alkoxy group (-OCHCH3CH3) on the silicone chain appears around 1640cm -1 The carbon-carbon double bond (C=C) stretching vibration absorption peaks on the left and right indicate that the double bond has undergone polymerization and the polymer emulsion has been successfully prepared.

[0042] The decorative waterproof integrated coating is prepared by the following production process:

[0043] (1) Mix filler, inorganic pigment and water-based resin dispersant K491, and grind them in a ball mill for 10 minutes to obtain colored filler;

[0044] (2) Place the polymer emulsion in a mixer. In stirring mode, add colored filler, diisobutyl nylonate, and water in order, and continue stirring for 3 minutes. Then add cement and continue stirring for 1 minute. Finally, add water-based defoamer DT-650 and continue stirring for 5 minutes. The stirring speed is 200 rpm.

[0045] Example 2

[0046] A decorative waterproof integrated coating comprises the following components by weight: 75 parts of polymer emulsion, 71 parts of cement, 5 parts of diisobutyl nylonate, 1.2 parts of water-based resin dispersant K491, 4 parts of water-based defoamer DT-650, 3 parts of inorganic pigment, 17 parts of filler and 13 parts of water.

[0047] The filler is calcium carbonate whisker, nano silicon dioxide and dolomite powder; the mass ratio of calcium carbonate whisker, nano silicon dioxide and dolomite powder is 25g:11g:4g.

[0048] The inorganic pigment is zinc iron yellow.

[0049] The cement is white silicate cement.

[0050] The polymer emulsion is prepared by the following steps:

[0051] S1, taking 60wt% of raw materials, mixing, stirring (stirring speed 1300r / min) and dispersing at 45°C for 9min to obtain a pre-emulsion; the raw materials include deionized water, disodium sulfosuccinate ethoxylated alcohol half ester, allyloxy cardanol sulfonate, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid and 3-methacryloxypropyl triisopropoxy silane;

[0052] S2, mixing the remaining raw materials and 30wt% of an initiator, heating to 80°C, stirring at a speed of 650r / min for 25min to obtain a seed emulsion; the initiator is dimethyl azobisisobutyrate;

[0053] S3, add the remaining initiator and pre-emulsion dropwise into the seed emulsion. After the addition is complete, stir the reaction at a speed of 400 r / min for 38 minutes, then raise the temperature to 88°C, keep the temperature for 8 minutes, and naturally cool to room temperature. Use sodium bicarbonate as a buffer to adjust the pH value to within 7.5, filter, and collect the filtrate to obtain a polymer emulsion.

[0054] The deionized water, disodium sulfosuccinate ethoxylated alcohol half ester, allyloxy cardanol sulfonate, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid, 3-methacryloxypropyl triisopropoxy silane, and initiator are used in the following ratios: 160 mL: 2.3 g: 0.5 g: 62 g: 20 g: 3.2 g: 3.9 g: 4.6 g: 0.5 g. The model of allyloxy cardanol sulfonate is DNS-86, the effective content is 25%, and the manufacturer is Guangzhou Double Bond Trading Co., Ltd.

[0055] The decorative waterproof integrated coating is prepared by the following production process:

[0056] (2) Mix the filler, inorganic pigment and water-based resin dispersant K491, and grind them in a ball mill for 15 minutes to obtain a colored filler;

[0057] (2) Place the polymer emulsion in a mixer. In stirring mode, add colored filler, diisobutyl nylonate, and water in order, and continue stirring for 4 minutes. Then add cement and continue stirring for 2 minutes. Finally, add water-based defoamer DT-650 and continue stirring for 7 minutes. The stirring speed is 250 rpm.

[0058] Example 3

[0059] A decorative waterproof integrated coating comprises the following components by weight: 80 parts of polymer emulsion, 75 parts of cement, 4-6 parts of diisobutyl nylonate, 1.5 parts of water-based resin dispersant K491, 5 parts of water-based defoamer DT-650, 3.5 parts of inorganic pigment, 18 parts of filler and 15 parts of water.

[0060] The filler is calcium carbonate whisker, nano silicon dioxide and dolomite powder; the mass ratio of calcium carbonate whisker, nano silicon dioxide and dolomite powder is 30g:12g:5g.

[0061] The inorganic pigment is zinc iron chrome brown.

[0062] The cement is white silicate cement.

[0063] The polymer emulsion is prepared by the following steps:

[0064] S1, taking 65wt% of raw materials, mixing, stirring (stirring speed 1500r / min) and dispersing at 50°C for 10min to obtain a pre-emulsion; the raw materials include deionized water, disodium sulfosuccinate ethoxylated alcohol half ester, allyloxy cardanol sulfonate, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid and 3-methacryloxypropyl triisopropoxy silane;

[0065] S2, mixing the remaining raw materials and 35wt% of an initiator, raising the temperature to 82°C, and stirring at a speed of 800r / min for 30min to obtain a seed emulsion; the initiator is dimethyl azobisisobutyrate;

[0066] S3, add the remaining initiator and pre-emulsion dropwise into the seed emulsion. After the addition is complete, stir the reaction at a speed of 450r / min for 45min, then raise the temperature to 90°C, keep warm for 10min, and naturally cool to room temperature. Use sodium bicarbonate as a buffer to adjust the pH value to within 8.0, filter, and collect the filtrate to obtain a polymer emulsion.

[0067] The deionized water, disodium sulfosuccinate ethoxylated alcohol half ester, allyloxy cardanol sulfonate, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid, 3-methacryloxypropyl triisopropoxy silane, and initiator are used in the following ratios: 180 mL: 2.5 g: 0.6 g: 72 g: 26 g: 3.8 g: 4.7 g: 5.3 g: 0.6 g. The model of allyloxy cardanol sulfonate is DNS-86, the effective content is 25%, and the manufacturer is Guangzhou Double Bond Trading Co., Ltd.

[0068] The decorative waterproof integrated coating is prepared by the following production process:

[0069] (3) Mix the filler, inorganic pigment and water-based resin dispersant K491, and grind them in a ball mill for 20 minutes to obtain a colored filler;

[0070] (2) Place the polymer emulsion in a mixer. In stirring mode, add colored filler, diisobutyl nylonate, and water in order, and continue stirring for 5 minutes. Then add cement and continue stirring for 3 minutes. Finally, add water-based defoamer DT-650 and continue stirring for 8 minutes. The stirring speed is 300 rpm.

[0071] Comparative Example 1

[0072] The same as Example 3, except that 3-methacryloxypropyltriisopropoxysilane was replaced with an equal molar amount of vinyltrimethoxysilane. The monomer conversion rate of the polymer emulsion in which vinyltrimethoxysilane participated was measured to be 93.5%, the gel fraction was 1.58, and the water absorption rate was 9.41%.

[0073] Comparative Example 2

[0074] The same as Example 3, except that an equal molar amount of acrylic acid was used instead of allylmalonic acid. The water absorption rate of the polymer emulsion in which acrylic acid participated was measured to be 7.38%.

[0075] Comparative Example 3

[0076] The same as Example 3, except that no dodecyl acrylate was added. The water contact angle of the polymer emulsion containing dodecyl acrylate was measured to be 72.23°, the water absorption rate was 10.45%, and the viscosity was 673 mPa·s.

[0077] Comparative Example 4

[0078] The same as Example 3, except that an equal mass of sodium vinyl sulfonate was used instead of allyloxy cardanol sulfonate. The monomer conversion rate of the polymer emulsion in which sodium vinyl sulfonate participated was measured to be 90.5%, the gel fraction was 1.72, and the ion stability failed.

[0079] Comparative Example 5

[0080] Same as Example 3, except that quinacridone pigment red is used instead of zinc iron chrome brown.

[0081] The decorative waterproof integrated coatings prepared in Comparative Example 5 and Example 3 were left to stand for 20 minutes. Figure 2 As shown. Figure 2 It can be seen that Figure 2 The a in the figure shows that the compatibility of quinacridone pigment red with the polymer emulsion in the decorative waterproof integrated coating in which quinacridone pigment red participates is poor, resulting in slurry coagulation of the polymer. Figure 2 The b in it shows that zinc iron chrome brown has good compatibility with polymer emulsion and is more suitable for the preparation of decorative waterproof integrated coating.

[0082] Performance testing

[0083] 1. The following performance tests were performed on the polymer emulsions prepared in Examples 1 to 3:

[0084] (1) Appearance of polymer emulsion: Take about 10.0 mL of polymer emulsion and apply it evenly on a clean glass plate with a film scraper. Visually inspect whether there are coarse particles and foreign matter in the polymer emulsion, and whether it is uniform and fine. If there are no coarse particles and foreign matter, and the polymer emulsion is uniform and fine, it is considered to have passed. Otherwise, it is considered to have failed.

[0085] (2) Viscosity test: Use a rotary viscometer to measure the viscosity of the polymer emulsion. Pour the polymer emulsion into a special container and place the container in a constant temperature water bath at 25°C; estimate the approximate viscosity of the polymer emulsion, select a suitable rotor and adjust it to a suitable speed; after installing the rotor, make sure that the rotor liquid level calibration line is submerged in the polymer emulsion to be tested; after switching to the automatic measurement mode, start the viscometer for testing and record the readings; measure each polymer emulsion three times. To ensure measurement accuracy, the data during the test should be between 30% and 100% of the range, and the average value is used as the viscosity of the emulsion to be tested.

[0086] (3) Emulsion stability

[0087] Ionic stability: Take 5 mL of polymer emulsion and place it in a 10 mL centrifuge tube, add 1 mL of 10 wt% calcium chloride solution, shake well and let it stand for 3 days to observe whether demulsification or stratification occurs. If there is no demulsification or stratification, the ionic stability test passes, otherwise it fails.

[0088] Mechanical stability: Take 50mL of polymer emulsion and place it in a container. Use a high-speed disperser to disperse it, gradually increase the speed, and finally stir and disperse it at a high speed of about 4000r / min for 20 minutes. Observe whether the emulsion breaks and the viscosity increases rapidly. If not, the mechanical stability test passes, otherwise it fails.

[0089] Freeze-thaw stability: Take 20 mL of polymer emulsion and place it in a sample bottle; then place the sample bottle in a freezer at -20±0.5℃ for 24 hours, then slowly thaw it at room temperature, and place it in a freezer at -20±0.5℃ for 24 hours after 5 hours, and repeat this cycle 4 times. Observe whether the polymer emulsion has demulsification or stratification. If not, the freeze-thaw stability test has passed, otherwise it has failed.

[0090] (4) Polymer emulsion particle size test: The polymer emulsion was mixed with deionized water in a ratio of 1:100, and the particle size was tested using a nanoparticle size analyzer and a Zeta potential analyzer, and the average particle size was calculated.

[0091] (5) Monomer conversion rate: The ratio of the measured solid content of the polymer emulsion to the theoretically calculated solid content is used to calculate the polymerization monomer conversion rate S. First, take an aluminum foil pan and weigh it as M0. Then, about 3 g of the polymer emulsion is taken into the aluminum foil pan and weighed as M1. The aluminum foil pan is then dried to constant weight and cooled to room temperature in a dryer and weighed as M2. The total mass of all comonomers M3 is weighed. The total mass of all comonomers M3 refers to the total mass of five comonomers in the polymer emulsion, namely, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid and 3-methacryloxypropyl triisopropoxysilane. The total mass of all substances except the comonomers M4 is weighed. M4 refers to the total mass of all substances in the polymer emulsion except the five comonomers, namely, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid and 3-methacryloxypropyl triisopropoxysilane. The measured solid content of the polymer emulsion is M, and the specific calculation formula is: ; The calculation formula for the polymerization monomer conversion rate is: .

[0092] (6) Gel rate: Collect the residues in the reaction flask and the stirring paddle after the reaction in S3, and dry them in a forced air drying oven at 100°C. Weigh the total mass of the dried gel as M5, and calculate the gel rate N according to the following formula: N = M5 / M3 × 100%.

[0093] (7) Water absorption rate: First, the prepared polymer emulsion was coated on a glass plate and allowed to dry and solidify at room temperature to form a film. Then, a portion of the latex film was immersed in deionized water for 30 days. The initial mass of the latex film before water absorption was weighed on an analytical balance as M6, and the final mass of the latex film after water absorption was weighed as M7. The water absorption rate X of the coating film can be obtained by the following formula: X = (M7-M6) / M6×100%:

[0094] (8) Water contact angle test: First, use a film-making apparatus to coat the polymer latex to be tested on a flat glass plate to make the surface of the prepared polymer latex film regular and flat. Then, drop deionized water on the latex film to measure the water contact angle.

[0095] The above test results are shown in Table 1:

[0096] Table 1. Polymer emulsion performance test results

[0097] Example 1 Example 2 Example 3 Emulsion appearance test pass pass pass Viscosity (mPa·s) 982 1023 1178 Ion stability pass pass pass Mechanical stability pass pass pass Freeze-thaw stability pass pass pass Emulsion particle size (nm) 208 215 230 Monomer conversion rate (%) 97.9 98.2 98.1 Gel rate (%) 0.85 0.91 0.79 Water absorption (%) 4.13 4.25 4.36 Water contact angle (°) 82.8 81.1 84.4

[0098] As can be seen from Table 1, the polymer emulsion prepared in the present application has a large monomer conversion rate, a low gel rate, a small water absorption rate, a strong stability, a moderate viscosity, and good hydrophobicity.

[0099] 2. According to the performance test method of GB / T23445-2009, the performance parameters of the decorative waterproof integrated coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 4 of the present application are measured and are shown in Table 2.

[0100] Table 2. Performance test results of decorative waterproof integrated coating

[0101] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Tensile strength (MPa) 2.54 2.68 2.62 2.21 2.05 2.24 2.13 Elongation at break (%) 182.5 188.3 179.7 154.8 133.6 141.5 148.9 Waterproofness (0.3MPa, 30min) impermeable impermeable impermeable impermeable impermeable impermeable impermeable Bond strength (MPa) 1.55 1.62 1.65 1.42 1.23 1.32 1.48 Impermeability (mortar water surface) (MPa) 1.28 1.33 1.31 1.08 0.61 0.78 0.69

[0102] It can be seen from Table 2 that the decorative waterproof integrated coatings prepared in Examples 1 to 3 of the present application have the characteristics of high tensile strength, high elongation at break, strong bonding strength, and excellent waterproof and anti-seepage properties.

[0103] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.

Claims

1. A decorative waterproof integrated coating, characterized in that: The components include the following by weight: 70-80 parts of polymer emulsion, 68-75 parts of cement, 4-6 parts of diisobutyl nylonate, 1-1.5 parts of water-based resin dispersant K491, 3-5 parts of water-based defoamer DT-650, 2.5-3.5 parts of inorganic pigment, 15-18 parts of filler, and 10-15 parts of water; The polymer emulsion is prepared by the following steps: S1, taking 55-65wt% of raw materials, mixing, stirring and dispersing at 40-50°C for 8-10min to obtain a pre-emulsion; the raw materials include deionized water, disodium sulfosuccinate ethoxylated alcohol half ester, allyloxy cardanol sulfonate, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid and 3-methacryloxypropyl triisopropoxy silane; S2, mixing the remaining raw materials and (25-35) wt% of the initiator, heating to 78-82°C, stirring for 20-30 minutes, to obtain a seed emulsion; S3, adding the remaining initiator and pre-emulsion dropwise to the seed emulsion, stirring and reacting for 30-45 minutes after the addition is completed, then heating to 85-90°C, keeping the temperature for 5-10 minutes, naturally cooling to room temperature, adjusting the pH value to 7.0-8.0, filtering, collecting the filtrate, and obtaining a polymer emulsion; The dosage ratio of the deionized water, ethoxylated alcohol half sulfosuccinate disodium, allyloxy cardanol sulfonate, isooctyl acrylate, methyl methacrylate, dodecyl acrylate, allyl malonic acid, 3-methacryloxypropyl triisopropoxy silane, and initiator is: (150-180) mL: (2-2.5) g: (0.40-0.6) g: (54-72) g: (15-26) g: (2.5-3.8) g: (3.2-4.7) g: (4.1-5.3) g: (0.3-0.6) g.

2. A decorative waterproof integrated coating according to claim 1, characterized in that: The initiator is dimethyl azobisisobutyrate.

3. A decorative waterproof integrated coating according to claim 2, characterized in that: In S3, sodium bicarbonate is used to adjust the pH.

4. A decorative waterproof integrated coating according to claim 3, characterized in that: The filler is calcium carbonate whisker, nano silicon dioxide and dolomite powder; the mass ratio of calcium carbonate whisker, nano silicon dioxide and dolomite powder is (20-30) g: (10-12) g: (3-5) g.

5. A decorative waterproof integrated coating according to claim 4, characterized in that: The inorganic pigment includes one or more of ultramarine blue, zinc iron yellow, zinc iron chrome brown, and chromium oxide green.

6. A decorative waterproof integrated coating according to claim 5, characterized in that: The cement is white silicate cement.

7. The production process of the decorative waterproof integrated coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Mix and grind the filler, inorganic pigment and water-based resin dispersant K491 for 10-20 minutes to obtain a colored filler; (2) Place the polymer emulsion in a mixer, and in stirring mode, add the colored filler, diisobutyl nylonate and water in sequence, continue stirring for 3-5 minutes, then add cement, continue stirring for 1-3 minutes, and finally add the water-based defoamer DT-650, and continue stirring for 5-8 minutes.

8. The production process of a decorative waterproof integrated coating according to claim 7, characterized in that: The stirring speed is 200-300 rpm.

Citation Information

Patent Citations

  • Coating composition for protecting concrete and method for manufacturing the same

    KR102199534B1